Posturografia dinâmica em indivíduos que trabalham na construção civil expostos à altitude. - Vieira, Gracielli Ribeiro (2006)
When exerting professional activities in the civil construction, the individuals play its functions, in the external extremities and walls of the buildings, being displayed to the height. They constantly use and with intensity the system initial, the visual system and the proprioceptivo system, thus being necessary a good integrity in these ways of information to prevent ackward conflicts and sensations and for consequences accidents in the work. The study it had as objective to verify through Posturografia Dinâmica (PD), in the individuals that work in the civil construction, displayed to the height, possible alterations in the dynamic corporal balance. This research was developed in the city of Florianópolis - SC. The experimental group (e) was composed for 127 individuals, with ages varying between 18 and 60 years, that work in the civil construction, exerting activities with exposition to the height. The group has controlled (c) was composed for 48 individuals with the same etária band of the group and, that they do not exert activities with exposition to the height. All the individuals had been submitted anamnese previous and evaluation of the dynamic balance through the PD for the method Foam-laser Dynamic Posturography, considered for Castagno (1994). In the test, the individuals had been displayed the conflict and corporal instability visual. With this we get a study of the functions of the systems initial, appearance, proprioceptivo. The analysis of the results found in you prop up through the PD in the individuals of Group C more is raised of the one than when compared with the results gotten in the individuals of the Group and the majority of the etárias bands, evidencing the necessity of new studies relating the balance in individuals displayed to the height, thus diminishing the risk of accidents in this activity